Answer: Option 'C' is correct.
Step-by-step explanation:
Since we have given that
![f(x)=2x^2+10x+12\\\\and\\\\g(x)=x+3\\\\\frac{2x^2+10x+12}{x+3}](https://tex.z-dn.net/?f=f%28x%29%3D2x%5E2%2B10x%2B12%5C%5C%5C%5Cand%5C%5C%5C%5Cg%28x%29%3Dx%2B3%5C%5C%5C%5C%5Cfrac%7B2x%5E2%2B10x%2B12%7D%7Bx%2B3%7D)
Now, we need to find the quotient of the given polynomial by dividing with g(x).
So, here we go:
Take out the common factor 2 from the numerator i.e. f(x), it becomes,
![2\left(x^2+5x+6\right)](https://tex.z-dn.net/?f=2%5Cleft%28x%5E2%2B5x%2B6%5Cright%29)
Now, we will apply the "Split the middle term", we get,
![\left(x^2+5x+6\right)\\\\=\left(x^2+2x\right)+\left(3x+6\right)\\\\=x\left(x+2\right)+3\left(x+2\right)\\\\=\left(x+2\right)\left(x+3\right)](https://tex.z-dn.net/?f=%5Cleft%28x%5E2%2B5x%2B6%5Cright%29%5C%5C%5C%5C%3D%5Cleft%28x%5E2%2B2x%5Cright%29%2B%5Cleft%283x%2B6%5Cright%29%5C%5C%5C%5C%3Dx%5Cleft%28x%2B2%5Cright%29%2B3%5Cleft%28x%2B2%5Cright%29%5C%5C%5C%5C%3D%5Cleft%28x%2B2%5Cright%29%5Cleft%28x%2B3%5Cright%29)
So, we will divide f(x) with g(x) :
![\frac{2\left(x+2\right)\left(x+3\right)}{x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cleft%28x%2B2%5Cright%29%5Cleft%28x%2B3%5Cright%29%7D%7Bx%2B3%7D)
Now, Cancel out the like term :
So, we get
![2\left(x+2\right)\\\\=2x+4](https://tex.z-dn.net/?f=2%5Cleft%28x%2B2%5Cright%29%5C%5C%5C%5C%3D2x%2B4)
Hence, Option 'C' is correct.